Sounds of scents: olfactory-auditory correspondences in the online purchase experience for perfume - Mahdavi, Mehdi; Barbosa, Belem; Oliveira, Zaíla; Chkoniya, Valentina (Review of Business Management, 2020)
Purpose – Perfume is arguably one of the most challenging experience products offered online. This article explores how the associations between the human senses of olfaction and audition can help consumers recognize the characteristics of the scent in the absence of the real scent. Method – Given the scarcity of contributions regarding online shopping behavior for perfume, an exploratory qualitative approach was implemented. Twenty-seven in-depth interviews were conducted among individuals from three countries with prior experience of purchasing perfume online. Results –The study highlights the associations made by the interviewees between the types of sounds/voice and types of scents and the complementary role of these cues in online shopping for perfume. Practical implications – Both e-sellers and e-buyers can benefit from the findings of this research. In fact, it is likely that e-shoppers decide to either consider or ignore an unknown perfume for purchase based on the scent signals perceived from sounds, which can provide guidance for e-sellers as well.